2003
DOI: 10.1189/jlb.0203067
|View full text |Cite
|
Sign up to set email alerts
|

Selective inactivation of CCR5 and decreased infectivity of R5 HIV-1 strains mediated by opioid-induced heterologous desensitization

Abstract: The opiates are well-established immunomodulatory factors, and recent evidence suggests that mu- and delta-opioid receptor ligands alter chemokine-driven chemotactic responses through the process of heterologous desensitization. In the present report, we sought to examine the capacity of mu- and delta-opioids to modulate the function of chemokine receptors CCR5 and CXCR4, the two major human immunodeficiency virus (HIV) coreceptors. We found that the chemotactic responses to the CCR1/5 ligand CCL5/regulated on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
73
1
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 52 publications
(55 reference statements)
7
73
1
1
Order By: Relevance
“…The opioid effect on chemokinemediated lymphocyte migration is better established; opioids incubated with leukocytes prevent cell movement toward chemokines [12]. These observations suggest interaction; in fact, cross-desensitization processes are described between the two receptor types [8,10].Here, we observed that the combination of DOR and CXCR4 ligands specifically abolished CXCR4-induced migration and adhesion of cell lines and of primary monocytes, and that the DOR antagonist naltrindole reversed this effect. These experiments also confirmed that DPDPE promotes potent MM-1 cell adhesion, which was greater than that promoted by CXCL12, and was blocked by simultaneous CXCL12 addition.…”
mentioning
confidence: 55%
See 3 more Smart Citations
“…The opioid effect on chemokinemediated lymphocyte migration is better established; opioids incubated with leukocytes prevent cell movement toward chemokines [12]. These observations suggest interaction; in fact, cross-desensitization processes are described between the two receptor types [8,10].Here, we observed that the combination of DOR and CXCR4 ligands specifically abolished CXCR4-induced migration and adhesion of cell lines and of primary monocytes, and that the DOR antagonist naltrindole reversed this effect. These experiments also confirmed that DPDPE promotes potent MM-1 cell adhesion, which was greater than that promoted by CXCL12, and was blocked by simultaneous CXCL12 addition.…”
mentioning
confidence: 55%
“…Chemokine receptors promote immune cell migration to and adhesion at the inflammation site, whereas opioid receptors reduce pain sensation on proximal nerve endings. Opioid receptors can also regulate the immune response, as they alter antibody responses, cell-mediated immunity, phagocytic activity, adhesion and chemotaxis [8][9][10][11]. Opioids also prevent leukocyte movement toward chemokine gradients [12], and cross-desensitization is described between opioid and chemokine receptors [8,10].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…CCR5 is upregulated in glia with HIV or SIV infection (Petito et al, 2001;Croitoru-Lamoury et al, 2003), suggesting Tat might increase CCL5-CCR5 signaling. By contrast, in monocytes or Chinese hamster ovary (CHO) cells, MOR or δ-opioid receptor activation causes heterologous desensitization of CCR5 and decreases infectivity by R5 HIV-1 strains (Szabo et al, 2003), suggesting that opiates attenuate CCL5-CCR5 signaling.…”
Section: Discussionmentioning
confidence: 99%